2022
DOI: 10.1002/sae2.12031
|View full text |Cite
|
Sign up to set email alerts
|

Frontiers in soil ecology—Insights from the World Biodiversity Forum 2022

Abstract: Global change is affecting soil biodiversity and functioning across all terrestrial ecosystems. Still, much is unknown about how soil biodiversity and function will change in the future in response to simultaneous alterations in climate and land use, as well as other environmental drivers. It is crucial to understand the direct, indirect and interactive effects of global change drivers on soil communities and ecosystems across environmental contexts, not only today but also in the near future. This is particul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 173 publications
0
13
0
Order By: Relevance
“…Additionally, soil microorganisms are important in improving soil physicochemical properties such as soil aggregate stability, porosity, aeration and soil organic matter (SOM) (Costa et al, 2018; Rashid et al, 2016) that are key to healthy agroecosystems. Further, there is an increasing understanding of the importance that soil biodiversity plays in maintaining ecosystem functioning (Delgado‐Baquerizo et al, 2016, 2020) and its management could be used to build more resource efficient and resilient food systems (Eisenhauer et al, 2022; El Mujtar et al, 2019; Bender et al, 2016; Bommarco et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, soil microorganisms are important in improving soil physicochemical properties such as soil aggregate stability, porosity, aeration and soil organic matter (SOM) (Costa et al, 2018; Rashid et al, 2016) that are key to healthy agroecosystems. Further, there is an increasing understanding of the importance that soil biodiversity plays in maintaining ecosystem functioning (Delgado‐Baquerizo et al, 2016, 2020) and its management could be used to build more resource efficient and resilient food systems (Eisenhauer et al, 2022; El Mujtar et al, 2019; Bender et al, 2016; Bommarco et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Eisenhauer et al [31] identified better data management, including data standardisation and integration, as one of the prominent research frontiers in soil ecology. This requires data standards (from the less expressive controlled vocabularies to the more expressive ontologies) to aid data harmonisation and compilation.…”
Section: Discussionmentioning
confidence: 99%
“…Compared to soil microbiota, data on soil fauna are scarce and often limited to ground-dwelling taxa (Burton et al, 2022). Soil fauna studies focusing on alpine and high-elevation habitats are especially rare.…”
Section: Key Aspectsmentioning
confidence: 99%